PENGARUH DAYA TARIK KONTEN AKUN INSTAGRAM @GENPIKOTAWARINGINBARAT TERHADAP KEPUTUSAN BERKUNJUNG KE DESTINASI WISATA DI KOTAWARINGIN BARAT - Chaidir Agro Dwi Putra Santoso, (2020)
The rapid development of technology and communication bring changes to the tourism sector, it makes it easy to promote tourist destinations to a wide audience through the attractiveness of content that is presented using digital containers such as through social media, such as Instagram. One of them is the Instagram account @genpikotawaringinbarat, an account that presents content about tourism in Kotawaringin Barat. The purpose of this study was to determine the effect and how much influence the level of attractiveness of Instagram @genpikotawaringinbarat account content on the decision to visit tourist destinations in West Kotawaringin. The theory used in this research is A-T-R (Awareness-Trial-Reinforcement). The approach used is quantitative explanatory using survey methods. The selected population was followers of the Instagram account @genpikotawaringinbarat with a total sample of 93 respondents, using a random sampling technique. The results of this study stated that Ha was accepted and Ho was rejected, there was an influence between the Attractiveness of the Instagram @genpikotawaringinbarat Account Content on the Decision to Visit Tourism Destinations in West Kotawaringin. Correlation test results obtained a correlation coefficient r value of 0.690 so that it can be interpreted that value has a strong relationship. The coefficient of determination shows the magnitude of the effect of 49.2% is the result of the contribution of the Instagram account content to visit decisions. As an account that is quite influential, Instagram @genpikotawaringinbarat is expected to be more innovative in developing more interesting and creative content so that it can increase public interest in making decisions to visit tourist destinations in West Kotawaringin.